The Effect of Emergency Situation Simulation on the Preparedness of Palu City Class IIA Detention Center Officers in response Earthquake Disaster - Arwan (YCAB Publisher, 2024)
Background: Indonesia's geographical location at the convergence of several tectonic plates makes it highly susceptible to various natural disasters, including earthquakes and tsunamis. Palu City, located in Central Sulawesi, is particularly vulnerable, as demonstrated by the devastating earthquake and tsunami that occurred on September 28, 2018. Objective: This study aims to improve the preparedness of officers at the Class IIA Palu Detention Center through targeted emergency simulation interventions. Methods: Employing a quasi-experimental one-group pretest-posttest design, the study involved all 75 officers registered at the detention center. Data were collected using pretest and posttest questionnaires, which assessed preparedness across five parameters based on the LIPI-UNESCO/ISDR framework (2006). Results: The findings revealed a significant improvement in the officers' preparedness levels, with the average preparedness score increasing from 14.21 before the intervention to 19.25 afterward. The Paired-Samples T-Test confirmed the effectiveness of the emergency simulation, yielding a p-value of 0.001. Conclusion: This study highlights the critical role of continuous emergency simulations in enhancing disaster preparedness. It emphasizes the importance of active involvement from both the community and officers for effective disaster management. Keywords: disaster preparedness; emergency simulation; earthquake response; correctional facility safety; public health management